Diagnosing the organizational culture of a Turkish pharmaceutical company based on the competing values framework - Demir, Cengiz; Unnu, Nazli A. Ayyildiz; Erturk, Emel (Journal of Business Economics and Management, 2011)
Organizational culture plays a significant role in understanding organizational dynamics and it distinguishes the members of one organization from other people. In this regard; it is found out that an organization, which is able to maintain a strong and “preferred” culture, is likely to enjoy many benefits such as higher levels of performance, person-organization fit, commitment, job satisfaction and competitive advantage. Thus, the purpose of this study is to diagnose the culture of a pharmaceutical company, which is located in Turkey, and find out the “perceived” and “preferred” cultural profiles both in the headquarters and branches of the company. The perceived culture has been found as hierarchy whereas the preferred one has been found as clan leading to incongruence between the perceived and preferred cultural profiles. In this regard; the reasons lying behind this mismatch are discussed, as it is important for the success of the organization and person-organization fit. Hence, the influential effects of national culture on shaping the organizational culture profiles have been discussed. Furthermore, the effects of educational level and union membership on culture profiles are also explored to understand the dynamics leading to such results thoroughly. Article in English. Turkijos farmacijos kompanijų organizacinės kultūros vertinimas, pagrįstas konkurencijos vertinimo sistema Santrauka. Straipsnyje teigiama, kad organizacine kultura vaidina svarbu vaidmeni ir kad ji suprantama kaip dinamine sistema. Buvo nustatyta, kad organizacija, pasižyminti stipria ir „priimtina” kultura, gali megautis daugeliu pranašumu, tokiu kaip didesnis našumas, tinkamumas, isipareigojimai, pasitenkinimas darbu bei konkurencinis pranašumas. Taigi šio tyrimo tikslas—nustatyti farmacijos bendroviu, isikurusiu Turkijoje, kulturą bei sužinoti „suvokiamos” ir „priimtinos” kultūros pobudį tiek centrinese bustinese, tiek ir jų filialuose. Reikšminiai žodžiai: organizacijos kultūra, konkurencingumo vertinimo sistema, turkų kultūra.